2022
DOI: 10.1002/ajmg.a.62889
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an association between Coffin‐Siris syndrome and congenital diaphragmatic hernia

Abstract: Coffin-Siris syndrome (CSS) is an autosomal dominant neurodevelopmental syndrome that can present with a variety of structural birth defects. Pathogenic variants in 12 genes have been shown to cause CSS. Most of these genes encode proteins that are a part of the mammalian switch/sucrose non-fermentable (mSWI/SNF; BAF) complex. An association between genes that cause CSS and congenital diaphragmatic hernia (CDH) has been suggested based on case reports and the analysis of CSS and CDH cohorts. Here, we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…14,15 To date, reports of SMARCC2 variants have been mostly part of individual case reports or large NDD studies with limited clinical information. [9][10][11][12][13]16 In an attempt to better characterize the clinical and molecular spectrum of SMARCC2-associated NDD, a large cohort of 65 cases was collected, including 41 novel individuals with de novo or inherited variants, whose clinical and molecular findings were systematically described, and 24 previously published individuals, whose data were thoroughly curated. Additionally, Human Phenotype Ontology (HPO) and automated facial recognition were used to investigate genotype-phenotype correlations between nontruncating and LGD variants, and structural modeling as well as functional assays to investigate missense variants.…”
Section: Constitutional Abolition Of Smarcc2 During Postnatal and Adu...mentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 To date, reports of SMARCC2 variants have been mostly part of individual case reports or large NDD studies with limited clinical information. [9][10][11][12][13]16 In an attempt to better characterize the clinical and molecular spectrum of SMARCC2-associated NDD, a large cohort of 65 cases was collected, including 41 novel individuals with de novo or inherited variants, whose clinical and molecular findings were systematically described, and 24 previously published individuals, whose data were thoroughly curated. Additionally, Human Phenotype Ontology (HPO) and automated facial recognition were used to investigate genotype-phenotype correlations between nontruncating and LGD variants, and structural modeling as well as functional assays to investigate missense variants.…”
Section: Constitutional Abolition Of Smarcc2 During Postnatal and Adu...mentioning
confidence: 99%
“…8,12 Three novel missense substitutions (c.2697G>T p.(Leu899Phe), c.640A>G p.(Thr214Ala), and c.1327C>T p.(Arg443Trp)) and one previously described splice variant (c.1651-2A>G p.?) 13 could not be further classified due to lack of conclusive evidence (no strong segregation information, recurrence, or strong effects in functional studies). Thus, carriers Ind-03, Ind-06, Ind-40, and Gofin_Subject 5 were excluded from further clinical analysis.…”
Section: Description Of Smarcc2 Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that somatic variants are not associated with CDH, and de novo germline variants of CDH‐associated genes can be found in 10%–30% of CDH patients, including those causing isolated CDH and those causing non‐isolated CDH 7 . Gofin et al 8 recently reported an association between genes that cause CSS and CDH. They provided the evidence in their own 5 patients and additional 12 cases from a review of the literature.…”
Section: Figurementioning
confidence: 99%